(untitled) (Journal of Hama University, 2024)
Introduction: The success of fixed restorations is linked to several important factors, including ensuring an ideal marginal and internal fit, and this requires ensuring a sufficient distance for the adhesive cement. Otherwise, it will cause many problems, including the accumulation of bacterial plaque, dissolution of the cement, the occurrence of periodontal disease, secondary caries, and dental sensitivity, which causes failure of the restoration. The aim of the study: evaluate the effect of the site of application of the die spacer on the internal fit of metal-ceramic prostheses Materials and Methods: The research sample consisted of 30 metal caps manufactured on supports in the shape of the first upper molar prepared to receive metal-ceramic crowns. The first group: the die spacer was applied to the occlusal surface and one-third of the axial surfaces. The second group: the die spacer was applied to the occlusal surface and two-thirds of the axial surfaces. The third group: the die spacer was applied to the occlusal surface and all of the axial surfaces except 0.5 mm above the finish line. The internal gap measurement was performed using the Cement Replica Technique Results: The results showed that there were statistically significant differences between the three test groups, where the third group (control) achieved the best internal fit. Conclusions: Applying the die spacer to the occlusal surface and all axial walls except 0.5 mm from the finish line achieved the best internal fit.